Lysozyme turnover in the rat - Hansen, Niels Ebbe; Karle, Hans; Andersen, Vagn (The Journal of Clinical Investigation, 1971)
Lysozyme turnover in the rat was studied with 125I-labeled rat lysozyme. It was found that plasma lysozyme has a rapid disappearance rate with a half-life of 75 min. The rate of synthesis was calculated at 3.4 μg/min per 100 g rat. This rate of synthesis was compared with figures from the literature for the turnover rate of neutrophilic granulocytes, and the data were consistent with the concept that disintegrating neutrophils are the main source of plasma lysozyme. The distribution of enzymatic lysozyme activity and of radioactive lysozyme was studied in several organs. Very high enzymatic activity was found in leukocytes as were considerable activities in lungs, kidneys, bone marrow, spleen, and intestine; little enzymatic activity was found in the urine. High radioactive levels as compared with plasma radioactivity were demonstrated only in the kidneys. This indicates that of the organs studied, the kidney is the predominant site of storage and destruction of plasma lysozyme. Lysozyme was found to disappear only slowly from the kidneys over a period of 4 days. The data obtained seem to indicate that lysozyme or a lysozyme degradation product precipitable by trichloroacetic acid was released in small amounts from the kidneys to plasma throughout this period.